Cyber communication : the legal risk of the employer / Norazlina Abdul Aziz, Irini Ibrahim - Abdul Aziz, Norazlina; Ibrahim, Irini (2012)
The direction of new communication technology has shaped a trend that requires every layers of the society to participate in its network activity. An exclusion of oneself in these linkages of activities may results in isolation from the society. In responding to this new culture, employers have provided facilities within their working environment for the employees to be able to access the network. Simultaneously, an overwhelming usage of the internet has contributed to uncontrollable activities which exposed harms to many private lives. This is a conceptual paper which outlined the potential legal risk of the employer relating to the illegal internet communication made by the employee. This emerging risk requires the diversion of management impose on the employer within their working space. The Malaysian legal framework in governing the rights and liabilities of the Employer on illegal communication through internet i.e. The Multimedia and Telecommunication Act 1998, Sedition Act 1948, Internal Security Act 1960, The Defamation Act 1957, and principles under the law of Tort will be highlighted. The study also requires the need to look into the advanced countries approach that could be of help to solve the inadequacy of the said laws. The objectives underlying this study is to examine the Malaysian legal standing on the rights and liabilities of the Employer in Malaysia under the illegal internet communication suits and looking into the approach taken by the advanced countries into solving the inadequacy of the said laws with the intention of recommending the most relevant amendment to the existing Malaysian legal framework on the liabilities and protection for the Employer.